Teknik Relaksasi Napas dalam terhadap Penurunan Nyeri Persalinan di Tempat Praktik Mandiri Bidan Andra Tahun 2024 - Adhika Wijayanti; Sartika Dwi Yolanda Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Labor is a complex interaction between psychological and physiological drives in women. (90%) delivery is accompanied by pain. In the active phase there is an increase in the intensity and frequency of contractions, so that the peak pain response is in this phase. Pain and soreness during labor are basically caused by strong contractions during labor. Breathing relaxation techniques can control pain by minimizing sympathetic activity in the autonomic nervous system. This study aims to determine the effect of deep breathing relaxation techniques on reducing labor pain in the first active phase. The type of design in this study is pre-experimental with The number of samples was taken according to the Accidental Sampling technique, samples were taken when patients went to the Andra Agustiana PMB Clinic with a minimum of 30 respondents. The data collection technique used a questionnaire sheet and a Numeric Rating Scale (NRS) pain scale. Data analysis used the Wilcoxon test. The results showed that before being given the breathing relaxation technique, most respondents experienced severe pain or pain levels on a scale of 7-10, namely 25 respondents (71.4%) and after being given deep breathing relaxation technique treatment, most respondents experienced moderate pain (scale 4-6) as many as 28 respondents (80%). The results of data analysis obtained the Asymp.significancy value = 0.000 (ρ<0.05). The conclusion is that there is an effect of providing deep breathing relaxation techniques on reducing labor pain in the first active phase. It is hoped that deep breathing relaxation techniques can be applied in the management of labor care as an alternative to reduce labor pain for mothers giving birth in the first active phase